Subsidy competition for FDI: Fierce or weak? - Tomáš Havránek (Charles University in Prague, Institute of Economic Studies (IES), 2009)
The objective of this paper is to empirically assess the recently introduced models of subsidy competition based on the classical oligopoly theories, using both cross-sectional and panel data. Three crucial scenarios (including coordination, weak competition, and fierce competition) are tested employing OLS, iteratively re-weighted least squares, fixed effects, and Blundell-Bond estimator. The results suggest that none of the scenarios can be strongly supportedalthough there is some weak support for cooperation, and thus that empirical evidence is not in accordance with the tested models. Further, it seems that by means of FDI incentives countries try to compensate foreign investors for high wages or low productivity of their citizens.
Keywords: C21; C23; F21; F23; H25; 330; Panel data; Investment incentives; Foreign direct investment; Subsidy competition; Subvention; Investitionspolitik; Standortwettbewerb; Direktinvestition